Predictive role of MGMT and IDH status in the efficacy of bevacizumab for high-grade glioma: a retrospective study - Bai Xuexue; Yan Chengrui; Wenbin Ma; Feng Ming; Wu Chao (Frontiers in Oncology)
BackgroundThe objective of this study is to investigate the predictive role of O6-methylguanine-DNA methyltransferase (MGMT) and isocitrate dehydrogenase (IDH) status on the efficacy of bevacizumab (BEV) in high-grade glioma (HGG), while excluding the interference of chemotherapy agents.MethodsA retrospective, single-center analysis was conducted on 103 patients with HGG who received BEV treatment. The enrolled patients were grouped based on their different biomarker statuses. Depending on whether the numerical variables of the patients satisfied the normal distribution, t-test or rank-sum test was employed. Chi-square test was used for the comparison of categorical variables. Univariate and multivariate Cox regression analyses were performed to identify prognostic factors affecting progression-free survival (PFS) and overall survival (OS).ResultsMultivariate COX regression analysis revealed that pathological grade, extent of resection, MGMT status, and IDH status were independent factors influencing PFS and OS in patients with HGG. The PFS, OS, and therapeutic response were superior in the MGMT methylated group compared to the unmethylated group. Similarly, patients with IDH mutations exhibited better PFS, OS, and therapeutic response than those with IDH wild-type.ConclusionsAfter controlling for potential confounding effects of chemotherapeutic agents, HGG patients with concurrent MGMT methylation and IDH mutations are likely to derive greater benefit from BEV treatment.